Evolusi pengendapan sedimen Kuarter di daerah utara Air Musi, Kota Palembang - Sumatera Selatan - Moechtar, Herman (Indonesian Journal on Geoscience, 2007)
http://dx.doi.org/10.17014/ijog.vol2no1.20071In the studied area, the sedimentary Quaternary facies consists of fl uvial channel separated by fl oodbasin, swamp, and fl oodplain deposits. Changes in channel style from channel 1, 2, and to 3 are interpreted as the result of a change in the type of river discharge from low to high sinuosity channels. Vertical changes in the character of these fl uvial channels can be related to changes in humidity. The lateral and vertical succession of the fl oodbasin and swamp environments shows evidence of decreasing and increasing of these facies. They are the result of changes in climate. Vertical changes of the Quaternary deposit successions can be related to changes in climate. It is concluded that the subinterval facies I.a to I.c as form of channel 2 and fl oodplain facies (subinterval facies I.b) refl ects a continuosly increase in climate from minimum to climatic maximum. Whereas, from the subinterval facies I.c to II.c during deposition of the subinterval facies II.b by the occurrence of fl oodbasin facies 2, the humid climate decreased from climatic maximum to minimum. Probably, this can be called as astrostratigraphy or orbital stratigraphy. Â  Â